Mathematical Modelling of the Highway Influence to Air Pollution - Daniela Durcanska; Ferdinand Hesek (Communications - Scientific letters of the University of Zilina, 2000)
The paper deals with the procedure of the highway project evaluation from the standpoint of highway influence to the environment. The official calculation methodology of air pollution is used for that purpose. The methodology was adjusted so that the differences of highways from the common roads were taken into consideration by the calculation of pollutant distribution in the surroundings of the highway, mainly from the high speed of the traffic stream point of view.